The Role of Strategic Thinking in the Productivity of the Ministry of Sports and Youth Using Structural Equation - Saeid Sorkheh; Reza Shajie; Shahram Alam; Nahid Shatab Bushehri (Research in Sport Management and Marketing, 2023)
The present research aimed to study the role of strategic thinking in the productivity of the Ministry of Sports and Youth using structural equation and applied with the mixed research method combined with an exploratory approach. In the qualitative part, Strauss and Corbin method and in the quantitative part, the structural equation modeling method have been used. The statistical population of the research in the qualitative part includes people with sport senior managements in the country, sport experts and policy makers, as well as sport management professors. The opinions of 15 experts have been obtained during a semi-structured interview until reaching theoretical saturation in a completely Non-probability way by using goal oriented theoretical and snowball techniques. In the quantitative part, between five and 10 samples were required for each item; Therefore, the statistical sample consisted of 294 subjects. There were 49 variables that were considered for the structural analysis of 6 samples for each variable.The data collection tool was a semi-structured interview in the qualitative part and a researcher-made questionnaire in the quantitative part. This research shows that the policies, solutions, programs and acts should be adjusted with a strategic approach, for fulfilling the awareness guidelines and with regard to the changes of the managers and human resources of the Ministry of Sports, towards constructing a collective memory it is recommended to establish a joint think tank between the human resources of the five current vice-chancellors of this ministry.